PERAN BADAN ARBITRASE PASAR MODAL INDONESIA DALAM PENYELESAIAN SENGKETA ALTERNATIF - Oktia Purnama Dewi, I Gst Agung Istri; Wirasila, A. A. Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper entitled “The Role of The Indonesian Capital Market Arbitration Board (BAPMI) In Alternative Dispute Resolution. This paper is motivated by the existence of alternative dispute resolution of capital markets that can solved through BAPMI. However, not enough people acknowledge the role and competency of BAPMI in resolving disputes in the capital market. This purpose of this paper is to explain the role BAPMI as mediators and to determine the role of BAPMI related to "binding opinion". It can be concluded that the role of BAPMI as mediator is only to facilitate meetings and negotiations within the framework of mediation with a goal to reach a settlement between the parties to the dispute. The role of BAPMI related to binding opinion is to assist the parties in interpreting a vague provision in the agreement, so the differences of interpretation between the parties will not be happening again which able to trigger any further dispute. This paper uses the juridical normative research method.
Keywords: Capital Market, Alternative Dispute Resolution, Indonesian Capital Market Arbitration Board